Microbiological analysis of cattle milk not industrialized marketed in Cajazeiras city, Paraíba - Abreu, Dandara Dias Cavalcante; Moésia, Renelita da Rocha (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2017)
The term milk product from the complete and uninterrupted milking, hygiene conditions, healthy cows, well fed and rested. Is the noblest products of animal origin, characterized as an opaque white liquid, more viscous than water, slightly sweet taste and odor little sharp. Because of having a high nutritional value, is a food widely consumed by humans, especially in children's diets. Because it is so rich in nutritional terms, it is also an excellent medium for microorganism growth and proliferation. This study aimed to identify the presence of bacteria that can be found in bovine milk sold in the city of Cajazeiras, Paraíba. 10 samples of cow's milk in natura. Heave of each sample was inoculated into Brain Heart Infusion broth and incubated in bacteriological incubator at 37 ° C for 24h. They were then plated in culture medium CPS ID Chromogenic (Biomériex), and again incubated for a further 24h. Bacteria grown were identified by the appearance of colonies through staining and confirmed by biochemical identification. We identified the presence of Klebsiella spp. and Escherichia coli. It was concluded therefore that the fresh milk sold in the city of Cajazeiras, Paraíba It has a high bacterial load.